The sustainable enterprise fieldbook : when it all comes together - Wirtenberg, Jeana; Russell, William G.; Lipsky, David (Routledge, Taylor & Francis Group, 2017)
"Today, managers and leaders of organizations, in both the private sector and civil society, are being challenged as never before to find ways to play a proactive role in addressing the concerns of sustainable development. But they are often overwhelmed by a bombardment of conflicting messages from the media, shareholders, customers, employees, and NGOs. The Sustainable Enterprise Fieldbook helps managers deal with this confusion. It teaches them how to strike a better balance, moving from an "either/or" mind-set to one that holistically embraces social, environmental and economic issues simultaneously. It addresses the "what" ("what is a sustainable strategy for a company or organization?") as well as the "how" ("how do we go about building a sustainable enterprise?"). The Sustainable Enterprise Fieldbook has been put together by an outstanding network of experts from business (Microsoft, Sony, Philips, and AIG), consultancies, and academia.-Resumé vydavatel
"First published 2008 by Greenleaf Publishing Limited"--Copyright page.
Keywords: podnikový management -- environmentální aspekty; udržitelný rozvoj; industrial management -- environmental aspects; sustainable development; kolektivní monografie; elektronické knihy; collective monographs; electronic books